Demonstrational Optics Part 2, Coherent and Statistical Optics - Marchenko, Oleg; Kazantsev, Sergi; Windholz, Laurentius (Springer US : Imprint: Springer, 2007)
Demonstrational Optics presents a new didactical approach to the study of optics. Emphasizing the importance of elaborate new experimental demonstrations, pictorial illustrations, computer simulations and models of optical phenomena in order to ensure a deeper understanding of wave and geometric optics. It includes problems focused on the pragmatic needs of students, secondary school teachers, university professors and optical engineers. Part 2, Coherent and Statistical Optics, contains chapters on interference, diffraction, Fourier optics, light quanta, thermal radiation (Shot noise and Gaussian light), Correlation of light fields and Correlation of light intensities. A substantial part of this volume is devoted to thermal radiation and its properties, especially with partial coherence. A detailed treatment of the photo-effect with respect to statistical properties leads to the basics of statistical optics. To illustrate the phenomena covered by this volume, a large number of demonstration experiments are described and discussed. In the chapters devoted to statistical phenomena computer simulations are described, the code of all relevant programs being included.